Determination of Antioxidant and Antimicrobial Properties of Abaca (Musa textilis Née) Pseudostem Extracts - Rodero, Jan Clarence Figueroa; Hernandez, Alliana Pauline Biscocho; Alcantara, Mary Grace Silvano; Balinado, Lloyd Ongpauco; Alimboyoguen, Agnes Baes (Asian Journal of Biological and Life Sciences, 2025)
Aim: Identify and quantify phytochemicals in pseudostem sap extracts of two Musa textilis varieties (Luno, Maguindanao) and evaluate antioxidant (DPPH, FRAP) and antimicrobial properties against selected bacterial and fungal strains. Results: Phytochemicals (flavonoids, phenols, quinones, tannins) detected; Luno showed 65.36–66.31% DPPH scavenging and 50–54.14% FRAP; Maguindanao showed 60.62–67.26% DPPH and 70.85–71.98% FRAP. Both showed no antimicrobial activity against tested strains. Conclusion: Solvent choice affects extraction; extracts display antioxidant potential.
Keywords: Abaca; Musa textilis; Antioxidant; DPPH; FRAP